Association between maternal obesity, essential fatty acids and biomarkers of fetal liver function. (March 2023) - Ortiz, Macarena; Sánchez, Francisca; Álvarez, Daniela; Flores, Cristian; Salas-Pérez, Francisca; Valenzuela, Rodrigo; Cantin, Claudette; Leiva, Andrea; Crisosto, Nicolás; Maliqueo, Manuel
Highlights: Maternal obesity affects the composition of fatty acids in maternal erythrocytes and placenta, which could impact on their bioavailability for maternal-fetal transfer. The composition of fetal VLDL lipoproteins from newborns of women with obesity is characterized by lower levels of stearic acid, suggesting modifications on fetal fatty acid metabolism. Maternal erythrocytes content of linoleic acid and alpha-linolenic acid are correlated with gamma-glutamyl (GGT) transferase activity in umbilical cord blood, indicating its relationship with fetal liver function. Abstract: Maternal obesity and the imbalance in linoleic acid (C18:2 n-6, LA) and alpha-linolenic acid (C18:3 n-3, ALA) levels are related with hepatic disturbances in the offspring. However, whether these alterations are present during fetal life is not well understood. Obese and normal weight pregnant women were recruited to determine fatty acids (FAs) consumption, FAs profile (in maternal erythrocytes, placenta and neonatal very low-density lipoproteins VLDL) and biomarkers of fetal liver function, such as gamma-glutamyl transferase (GGT), alpha-fetoprotein (AFP) and albumin, in umbilical cord blood. Stearic acid (C18:0, ST) was lower, and total n-3 FAs tended to be lower in umbilical cord VLDLs of obese women compared to controls. Independently of maternal obesity, GGT levels in umbilical cord blood was positively correlated with the LA content and negatively correlated with the ALA content in maternal erythrocytes. We conclude that maternal obesity and its imbalance of LA and ALA are associated with changes in biomarkers of fetal liver function.